2022
DOI: 10.1002/fsn3.2957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different iron treatments on wine grape berry quality and peel flavonoid contents

Abstract: In this study, eight‐year‐old wine grape plants (Cabernet Sauvignon) were subjected to five different iron treatments: ferrous sulfate, ferric ethylenediaminetetraacetic acid (EDTA‐Fe), ferric citrate, ferric gluconate, and ferric sugar alcohol, and conventional fertilization. Foliar spraying with clear water was used as the control treatment. The effects of different iron treatments on berry quality and flavonoid accumulation in grape peels were explored. All five iron treatments affected the sugar, acid, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Leaf spraying mainly involves spraying yellowing leaves with iron salt solutions (iron citrate, EDHA-Fe (ethylene diamine tetraacetic acid-Fe), ferrous sulfate and so on), which can improve the yellowing disorder of plants, such as kiwifruit under the treatment of iron citrate and iron amino acid complex, which can Mechanism II of plant root uptake and response to Fe deficiency stress. Ning et al 10.3389/fpls.2023.1190768 effectively improve the chlorophyll content and the content of vitamin C, solids and whole iron in fruits and improve fruit (Wang et al, 2011); the foliar spray of ferric citrate balanced the sugar-acid ratio of grape berries and increased the contents of anthocyanins, flavanols, and flavonols in grape skins (Zhang et al, 2022); after the application of iron fertilizer complex containing iron citrate Fe and EDDHA-Fe, it effectively increased the content of active Fe in peanuts at the flowering hypocotyl and ripening stages and also significantly increased the content of whole Fe in leaves and kernels (Liu et al, 2016); in using different combinations of ferrous sulfate with amino acids (AA), urea (Urea), and EDTA-2Na (disodium ethylene diamine tetraacetic acid) chelated Fe for yellowing apple fruit trees. In the buried bottle and foliar spray experiments, it was found that buried bottle with foliar spray of Fe-EDTA-Urea significantly corrected apple yellowing by increasing the relative chlorophyll content, improving photosynthetic performance, and increasing iron utilization (Guo et al, 2018).…”
Section: Application Of Plant Iron Fertilizermentioning
confidence: 99%
“…Leaf spraying mainly involves spraying yellowing leaves with iron salt solutions (iron citrate, EDHA-Fe (ethylene diamine tetraacetic acid-Fe), ferrous sulfate and so on), which can improve the yellowing disorder of plants, such as kiwifruit under the treatment of iron citrate and iron amino acid complex, which can Mechanism II of plant root uptake and response to Fe deficiency stress. Ning et al 10.3389/fpls.2023.1190768 effectively improve the chlorophyll content and the content of vitamin C, solids and whole iron in fruits and improve fruit (Wang et al, 2011); the foliar spray of ferric citrate balanced the sugar-acid ratio of grape berries and increased the contents of anthocyanins, flavanols, and flavonols in grape skins (Zhang et al, 2022); after the application of iron fertilizer complex containing iron citrate Fe and EDDHA-Fe, it effectively increased the content of active Fe in peanuts at the flowering hypocotyl and ripening stages and also significantly increased the content of whole Fe in leaves and kernels (Liu et al, 2016); in using different combinations of ferrous sulfate with amino acids (AA), urea (Urea), and EDTA-2Na (disodium ethylene diamine tetraacetic acid) chelated Fe for yellowing apple fruit trees. In the buried bottle and foliar spray experiments, it was found that buried bottle with foliar spray of Fe-EDTA-Urea significantly corrected apple yellowing by increasing the relative chlorophyll content, improving photosynthetic performance, and increasing iron utilization (Guo et al, 2018).…”
Section: Application Of Plant Iron Fertilizermentioning
confidence: 99%
“…All treatments were irrigated using a drip irrigation system and management practices such as pruning and pest control were consistent. The chemical properties of the soils (0-40 cm depth) (Supplementary Table S1) were determined as described by Wang et al [24]. The length of the shoot was measured using a 5 m measuring tape.…”
Section: Treatment Experimental Design and Samplingmentioning
confidence: 99%
“…However, due to the poor nature of the soil in this region, fertilization is an inevitable means of increasing productivity. Several studies on the effect of fertilization have been published [9,13,[19][20][21][22], but most of these studies are focused on single fertilization, while few studies on the effect of organic fertilizer on grape quality are reported [19,23,24]. Moreover, long-term usage of single fertilizers depletes soil organic matter and causes the imbalance of soil nutrients, affecting grape aroma formation and reducing grape quality, consequently lowering the wine quality.…”
Section: Introductionmentioning
confidence: 99%